Pelatihan Media Siber Dalam Rangka Peningkatan Kapasitas Literasi Media Pekebun Dalam Mendukung Program Sawit Rakyat Bersinergi Dengan ISPO - Herlon, Meki; Ridho, Zulhamid; Kausar, Kausar; Arifuddin, Arifuddin; Retuhadi, Fajar; Rosnita, Rosnita; Yulida, Roza; Andriani, Yulia; Muwardi, Didi; Septya, Fany; Bakar, Mustaqim Abu; Andriana, Hanifaturrahmi; Phreti, Phreti; Hidayat, Imam; Hamidi, M. Rasyid (Unri Conference Series: Community Engagement, 2024)
The community of Lubuk Bendahara Village on oil palm plantations for their livelihood. Currently, the oil palm farmers are organized into five active farmer groups. The implementation of sustainable plantation practices, as required by the Indonesian Sustainable Palm Oil (ISPO) certification, presents both a challenge and a necessity for these farmers. According to Presidential Regulation No. 44 of 2020 and the Ministry of Agriculture Regulation No. 38 of 2020, companies and independent farmers must adopt sustainable practices by 2025. This situation requires the farmer groups to continually update their information. Website serves as an effective information system, providing accurate and beneficial information to enhance the role of these groups. The purpose of this community service activity is to provide training on the use of the website luben.id, managed by the village and the farmer groups. The website contains information about the village profile, farmer groups, ISPO materials, and details about oil palm plantations. This activity, conducted from July to August 2024, involves MBKM student interns as agents of change. The outcomes include the establishment of website management, knowledge transfer, and enhanced media literacy among palm oil farmers, particularly in accessing information to support ISPO implementation.